The Relation between Market Values, Earnings Forecasts, and Reported Earnings* - Begley, Joy; Feltham, Gerald A. (Contemporary Accounting Research, 2002)
Abstract Recently, much of the research into the relation between market values and accounting numbers has used, or at least made reference to, the residual income model (RIM). Two basic types of empirical research have developed. The “historical” type explores the relation between market values and reported accounting numbers, often using the linear dynamics in Ohlson 1995 and Feltham and Ohlson 1995 and 1996. The “forecast” type explores the relation between market value and the present value of the book value of equity, a truncated sequence of residual income forecasts, and an estimate of the terminal value at the truncation date. The analysis in this paper integrates these two approaches. We expand the Feltham and Ohlson 1996 model by including one‐ and two‐period‐ahead residual income forecasts to infer “other” information regarding future revenues from past investments and future growth opportunities. This approach results in a model in which the difference between market value and book value of equity is a function of current residual income, one‐ and two‐period‐ahead residual income, current capital investment, and start‐of‐period operating assets. The existence of both persistence in revenues from current and prior investments and growth in future positive net present value investment opportunities leads us to hypothesize a negative coefficient on the one‐period‐ahead residual income forecast and a positive coefficient on the two‐period‐ahead residual income forecast. Our empirical results strongly support our hypotheses with respect to the forecast coefficients.